Analysis On Drug Crime Distribution (G List) Kind Of Narcotics (Case Study In Court Decision In Region III Cirebon) - Iin Khaeriyatun Ni'mah; Sukarmi Sukarmi (Jurnal Daulat Hukum, 2019)
The problems of this study are: 1) How is the consideration and commitment of judges in the State Court in lowering the crime of trafficking of drudgs (G List)? 2) What are the constraints in finding criminal offense trafficking of drudgs (G List)? 3) How do the efforts and solutions should be executed against the crime of trafficking of drudgs (G List)? Method sociological approach juridical law and specification in this study were included descriptive qualitative, The sources and types of data in this study are primary data obtained from interviews with field studies Security Chief Penitentiary (KPLP) Narcotics Prison Cirebon, And secondary data obtained from the study of literature. The problems studied by the theory of law enforcement, legal protection and law enforcement.Results of the discussion concluded: Considerations and commitment of judges in the State Court in lowering the crime of trafficking of drudgs (G List) is to explicitly give appropriate consideration to the evidence in court, and a commitment to provide deserving punishment against criminal trafficking of drudgs G List. Obstacles in finding criminal offense trafficking of drudgs (G List) can be divided into the causes of the dealers and the causes of the user side, while the limiting factor of the dealers, namely Factors Poor Understanding of Law, Economic Factors, Environmental Factors Society, Factor Surveillance as well as factor constraints of the users, namely lack of evidence to arrest and lack Guide Report from Community. Efforts and solutions should be executed against the crime of trafficking of drudgs (G List) is through legal counseling on the dangers of drug distribution of G List, Doing arrest on drug users G List then perform a search pusher G List, Cooperate with BPOM in drug distribution of G List.Keywords: Crime; Distribution; Drug; G List; Narcotics.